"If you cannot tolerate that risk, you should never become a physician": a qualitative study about existential experiences among physicians. Issue 11 (30th October 2008) - Aase, M; Nordrehaug, J E; Malterud, K
Abstract : Background and objectives: Physicians are exposed to matters of existential character at work, but little is known about the personal impact of such issues. Methods: To explore how physicians experience and cope with existential aspects of their clinical work and how such experiences affect their professional identities, a qualitative study using individual semistructured interviews has analysed accounts of their experiences related to coping with such challenges. Analysis was by systematic text condensation. The purposeful sample comprised 10 physicians (including three women), aged 33–66 years, residents or specialists in cardiology or cardiothoracic surgery, working in a university hospital with 24-hour emergency service and one general practitioner. Results: Participants described a process by which they were able to develop a capacity for coping with the existential challenges at work. After episodes perceived as shocking or horrible earlier in their career, they at present said that they could deal with death and mostly keep it at a distance. Vulnerability was closely linked to professional responsibility and identity, perceived as a burden to be handled. These demands were balanced by an experience of meaning related to their job, connected to making a difference in their patients' lives. Belonging to a community of their fellows was a presupposition for coping with the loneliness and powerlessness related to their vulnerable professional position. Conclusions: Physicians' vulnerability facing life and death has been underestimated. Belonging to caring communities may assist growth and coping on exposure to existential aspects of clinical work and developing a professional identity.